Implications of Probiotics on the Maternal-Neonatal Interface: Gut Microbiota, Immunomodulation, and Autoimmunity - Swartwout, Brianna; Luo, Xin M. (Frontiers in Immunology, 2018)
Investigating probiotic microorganisms for treating autoimmune diseases is being conducted. The target of probiotic therapy is re-balancing the immune system after the ravages of dysbiosis. Specifically, probiotics for maternity are emerging on the market and have gained significant momentum in the literature. Some controversy surrounds whether probiotics administered maternally or during infancy are healthful for allergic disease, and their use for autoimmunity is relatively unexplored. Currently, no studies exist on the implications of maternal probiotics for the outcome of pregnancy in autoimmune disease. This review aims to discuss the use of maternal probiotics in health and autoimmune disease and to investigate their immunomodulatory properties.